2019
DOI: 10.1590/1983-21252019v32n405rc
|View full text |Cite
|
Sign up to set email alerts
|

Coating Seeds With Silicon Enhances the Corn Yield of the Second Crop

Abstract: The application of silicon is becoming popular in agriculture as an alternative for integrated crop management, owing to the diverse benefits resulting from the accumulation of silicon in grasses and the resultant resistance conferred in plants against biotic and abiotic stresses. The objective of this study was to evaluate whether the application of silicon, via seed coating and leaf application, influences the production and yield components of maize in the second crop. The experimental design was divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…The practical application of Si-rich products provides for an increase in plant productivity and the reduction of nutrient leaching (Matichenkov et al 2020). Use of phyllosilicate via seed coating increased the production components and yield of the second corn crop (Rodrigues et al 2019). The selected plant growth, yield and biochemical parameters of P. vulgaris were efficiently increased by combined PGPR and silicon fertilization under saline stress in which the marketable value of the crop can be improved (Kumar et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The practical application of Si-rich products provides for an increase in plant productivity and the reduction of nutrient leaching (Matichenkov et al 2020). Use of phyllosilicate via seed coating increased the production components and yield of the second corn crop (Rodrigues et al 2019). The selected plant growth, yield and biochemical parameters of P. vulgaris were efficiently increased by combined PGPR and silicon fertilization under saline stress in which the marketable value of the crop can be improved (Kumar et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…One alternative for lessening the damage caused by water and salt stress is the use of attenuators such as silicon, since this element has several effects on plants, among them resistance to abiotic stresses (ROMA-ALMEIDA et al, 2016). Most of the benefi ts of silicon are due to its being deposited on the cell wall beneath the leaf cuticle, in the form of amorphous silica (SiO 2 .nH 2 O) (FREITAS et al, 2011), forming a cuticle-silica double layer that acts as a protective barrier, reducing water loss in the plant by evapotranspiration (RODRIGUES et al, 2019). In their studies with Si nanoparticles as seed priming, Hussain et al (2019) observed that Si stimulated the activity of antioxidant enzymes and reduced the concentration of ROS (reactive oxygen species), which positively impacted the growth of wheat plants.…”
Section: Introductionmentioning
confidence: 99%
“…Número de fileiras de grãos por espigas produzidas por plantas de milho tratadas e não tratadas com silício crescidas na ausência de insetos, e de plantas submetidas à alimentação de insetos infectantes e sadios Médias seguidas da mesma letra não diferem entre si, pelo teste de Tukey a 5% de significância Tabela 13. Peso total de grãos (g) produzidos por plantas de milho tratadas e não tratadas com silício crescidas na ausência de insetos, e de plantas submetidas à alimentação de insetos infectantes e sadios Médias seguidas da mesma letra não diferem entre si, pelo teste de Tukey a 5% de significância Em ensaios semelhantes àqueles aqui realizados,Rodrigues et al (2019) relataram que a aplicação de silício em plantas de milho promoveu aumento no número de fileiras, o que gerou maior produtividade. Entretanto, experimentos conduzidos por Martins (2021) revelaram resultados concordantes com aqueles obtidos no presente trabalho, os quais mostraram ausência de diferença significativa entre o número de fileiras de grãos produzidas por plantas tratadas e não tratadas com silício.…”
unclassified